POSTOPERATIVE COMPLICATIONS OF ORBITAL TUMOR REMOVAL IN SARDJITO GENERAL HOSPITAL: Oral Presentation - Observational Study - Resident - Prasthiti Dewi Hasdini (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Orbital tumor removal surgery represent a small but significant portion of ophthalmologic surgery, and few reports of the associated complications are available. The aim of this study is to report the complications of orbital tumor removal surgery in Sardjito General Hospital, Yogyakarta. Methods : Descriptive retrospective study was carried out 138 patients who undergone orbital tumor removal surgery during July 2021-March 2023. Surgery approach and postoperative complications were collected from medical record. Results : Of approximately 138 patients, 12 (8%) patients had postoperative complications. Five (5%) of 75 patients who undergone anterior orbitotomy had postoperative complications. One percent had lagophthalmos, 1% had ptosis, 2% had decreased vision, and 1% had ocular movement disorders. Lateral orbitotomy was done in 21 patients. Three (12%) patients had postoperative complications. Four percent had ptosis, 4% had decreased vision, and 4% had ocular movement disorders. Four (60%) of 6 patients who undergone medial orbitotomy had ptosis (16%) and decreased vision (50%). Posterior orbitotomy was done in 8 patients. One (12,5%) patient had complication of ptosis. Conclusion : Anterior orbitotomy was the most common surgery approach for orbital tumor removal. The most common postoperative complications were ptosis and decreased vision. Informed consent is an important aspect to improve patient’s knowledge of postoperative complications.